Potential Unintended Consequences of a Conservative Management Strategy for Patent Ductus Arteriosus. (20th July 2015) - Elhoff, Justin J.; Ebeling, Myla; Hulsey, Thomas C.; Atz, Andrew M.
Abstract: Background: A recent review supports a strategy of deferring treatment of patent ductus arteriosus (PDA) in the preterm neonate until at least the second week after birth. In light of previous suggestion that later initiation of treatment may be less efficacious for closing PDAs it is reasonable to question if delayed treatment may be less effective. Design: We conducted a single center retrospective review of a neonatal intensive care unit database of infants ≤37 weeks gestation with the diagnosis of PDA and treated with indomethacin from 1999 to 2007. We determined gestational age (GA), timing of indomethacin initiation, and status of the PDA at hospital discharge. Treatment failure was defined as neonates requiring further intervention to close their PDA or those who died without echo‐proven PDA closure. Results: Of the 341 infants meeting the study criteria, 77 (23%) had defined treatment failure. The failure group had a younger median GA of 25 weeks (interquartile range [IQR], 24–26) vs. 28 weeks (IQR, 26–30) for the successful group ( P < .0001). The failure group had a median treatment initiation on day of life (DOL) 4 (IQR, 1–8) compared with DOL 3 (IQR, 1–6) for those in the successful group ( P = .15). Taken as a whole, infants treated after DOL 5 were significantly more likely to have treatment failure (30.1% vs. 19.3% for those treated DOL 1–5, P = .03). Conclusions: Our study confirms that younger GA at birth is correlated with increased likelihood of failed PDA closure. We also show a trend indicating that later initiation of treatment may decrease the chances of successfully closing a PDA. Future examination of PDA management should consider the potential unintended consequences that may accompany a delayed treatment strategy.